Determinants of willingness to venture into urban farming among Malaysian Urban Citizens: A quantitative analysis based on the theory of planned behaviour - Faghiri, Hamed; Yusop, Zulkornain; Mohamed, Zainal Abidin (Journal of Islamic, Social, Economics and Development, 2025)
Urban farming has gained prominence as a strategic response to Malaysia’s rising food security concerns, urban sustainability challenges, and increasing dependency on external food sources. Despite these pressing national needs, public willingness to engage in urban farming remains low, prompting the need for a focused behavioural investigation. This quantitative study examines the determinants influencing Malaysian urban citizens’ willingness to venture into urban farming (WLN) using the Theory of Planned Behaviour (TPB) as the guiding framework. A structured questionnaire, developed from qualitative insights and validated through pilot testing, was administered to 200 urban residents across ten major cities in Peninsular Malaysia. Partial Least Squares Structural Equation Modelling (PLS-SEM) using SmartPLS 4 was employed to test the relationships between five key constructs: Awareness (AWR), Non-Monetary Benefits (NMB), Monetary Benefits (MBS), Interest (INT), and Barriers and Challenges (BAR). The findings indicate that AWR and NMB are the strongest predictors of WLN, highlighting the roles of knowledge, environmental consciousness, social engagement, and perceived lifestyle improvement in shaping behavioural intention. MBS and INT also demonstrated significant positive effects, suggesting that individuals are additionally motivated by economic gains and personal enthusiasm for farming activities. Conversely, BAR was found to have an insignificant influence, implying that perceived obstacles such as space limitations, time constraints, or technical concerns do not substantially inhibit intention when motivational factors are strong. These results reinforce the relevance of the TPB framework in explaining pro-environmental behaviour and contribute to theoretical understanding by extending TPB into the domain of urban agriculture in a tropical, developing-country context. The findings provide actionable insights for policymakers, urban planners, and industry stakeholders to prioritize awareness-raising initiatives, community-based programs, training opportunities, and economic incentives to strengthen Malaysia’s urban farming ecosystem.